Gender and the professional predicament in nursing - Davies, Celia (Open Univ. Press, 1995)
Gender and the Professional Predicament in Nursing examines the ways in which our understanding of nursing is gendered, and how our notion of nursing is connected to our idea of what it is to be a woman. It explores the implications this connection has for the status of nursing as a profession, and re-examines some of the fundamental questions that the nursing profession has tried to address, such as: what is nursing care?; who should do it? and why is it so difficult to manage the provision of nursing care? Gender and the Professional Predicament in Nursing demonstrates that once nurses try to define and shape the nature of their work they are marginalized or silenced. Frequent descriptions of them as 'sentimental', 'divided' or 'incompetent' highlight the need to understand nurses' exclusion from policy debates, and why their voices are so seldom heard